Circulatory Metabolomics Reveals the Association of the Metabolites With Clinical Features in the Patients With Intrahepatic Cholestasis of Pregnancy - Liu, Wenhu; Wang, Qiang; Chang, Jinxia; Bhetuwal, Anup; Bhattarai, Nisha; Ni, Xin (Frontiers in Physiology, 2022)
Objective: Intrahepatic cholestasis of pregnancy (ICP) is associated with an increased risk of adverse pregnancy to the mother and fetus. As yet, the metabolic profiles and the association of the clinical features remain obscure. Methods: Fifty-seven healthy pregnant women and 52 patients with ICP were recruited in this study. Plasma samples were collected from pregnancies who received prenatal care between 30 and 36 weeks. Untargeted metabolomics to portray the metabolic profiles were performed by LC/MS. Multivariate combined with the univariate analysis was performed to screen out differential metabolites between the ICP and control groups. A de-biased sparse partial correlation (DSPC) network analysis of differential metabolites was conducted to explore the potential mutual regulation among metabolites on the basis of de-sparsified graphical lasso modeling. The pathway analysis was carried out using MetaboAnalyst. Linear regression and Pearson correlation analysis was applied to analyze correlations of bile acid levels, metabolites, newborn weights, and pregnancy outcomes in ICP patients. Results: Conspicuous metabolic changes and choreographed metabolic profiles were disclosed: 125 annotated metabolites and 18 metabolic pathways were disturbed in ICP patients. DSPC networks indicated dense interactions among amino acids and their derivatives, bile acids, carbohydrates, and organic acids. The levels of total bile acid (TBA) were increased in ICP patients with meconium-stained amniotic fluid (MSAF) compared with those without MSAF. An abnormal tryptophan metabolism, elevated long chain saturated fatty acids and estrone sulfate levels, and a low-antioxidant capacity were relevant to increased bile acid levels. Newborn weights were significantly associated with the levels of bile acids and some metabolites of amino acids. Conclusion: Our study revealed the metabolomic profiles in circulation and the correlation of the metabolites with clinical features in ICP patients. Our data suggest that disturbances in metabolic pathways might be associated with adverse pregnancy outcomes.